Diagnosis and intervention program for Burnout syndrome teachers in primary education district Huaraz and Independencia (2009) - Yslado M., Rosario (2010)
The general objectives of this study were both the frequency and characteristics of the Burnout syndrome in primary school teachers with experience equal to or greater than five years of public institutions in the districts of Huaraz and Independence, as planning and evaluating results of a psychoeducational intervention program. The pre –experimental study with pre and post test, with one group. In a sample of 133 teachers, 08 teachers were selected women, according to inclusion criteria. We used the survey and a questionnaire that included demographics and Maslach Scale - ED. Some conclusions were: 1) Teachers have “Burnout” in the initial stages (78.2%), intermediate (2.3%) and final (19.5%) 2) The psychoeducational intervention program applied to cases of Burnout in the final stage (VII) has been significantly effective in reducing emotional exhaustion (83.3%).